Quorum Sensing System of Ruegeria mobilis Rm01 Controls Lipase and Biofilm Formation - Su, Ying; Tang, Kaihao; Liu, Jiwen; Wang, Yan; Zheng, Yanfen; Zhang, Xiao-Hua (Frontiers in Microbiology, 2019)
Quorum sensing (QS) promotes in situ extracellular enzyme (EE) activity via the exogenous signal N-acylhomoserine lactone (AHL), which facilitates marine particle degradation, but the species that engage in this regulatory mechanism remain unclear. Here, we obtained AHL-producing and AHL-degrading strains from marine particles. The strain Ruegeria mobilis Rm01 of the Roseobacter group (RBG), which was capable of both AHL producing and degrading, was chosen to represent these strains. We demonstrated that Rm01 possessed a complex QS network comprising AHL-based QS and quorum quenching (QQ) systems and autoinducer-2 (AI-2) perception system. Rm01 was able to respond to multiple exogenous QS signals through the QS network. By applying self-generated AHLs and non-self-generated AHLs and AI-2 QS signal molecules, we modulated biofilm formation and lipase production in Rm01, which reflected the coordination of bacterial metabolism with that of other species via eavesdropping on exogenous QS signals. These results indicate that R. mobilis is one of the participators regulating marine particle degradation via QS-based interspecies signaling.